Analisis Kontribusi Retribusi Pariwisata Terhadap Pendapatan Asli Daerah Sebelum Dan Sesudah Pandemi Covid-19 - Nina Purwaningsih; Suci Nasehati Sunaningsih (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
The research carried out is a study of the level of retribution contributions from the tourism sector to Local Revenue before and after the Covid-19 pandemic. This research was conducted in the tourism sector in Magelang Regency. This study was carried out to know the level of contribution of the tourism sector retribution to local revenue before and after the Covid-19 pandemic in the Magelang Regency government. This research is descriptive quantitative research. The data used are secondary data obtained from BPPKAD Magelang Regency, BPS Magelang Regency, and DISPARPORA Magelang Regency. The results showed a decrease in the contribution of retribution for recreation and sports to Local Revenue receipts after the Covid-19 pandemic. The contribution of retribution for recreation and sports to Local Revenue in 2019 shows a figure of 1.38%, while in 2020 it shows a figure of 0.50%. This figure shows a decrease in the contribution of levies for recreation and sports after the Covid-19 pandemic. This happened because of social restrictions in the community which in the end resulted in a decrease in tourism sector income and the number of visitors to tourist objects in Magelang Regency. Keywords: Retribution For Recreation And Sports, Local Revenue, Covid-19